2017
DOI: 10.4142/jvs.2017.18.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Temporal changes in mammalian target of rapamycin (mTOR) and phosphorylated-mTOR expressions in the hippocampal CA1 region of rat with vascular dementia

Abstract: Mammalian target of rapamycin (mTOR) has an important role in various biological processes in cells. In the present study, we investigated temporal changes in mTOR and phosphorylated-mTOR (p-mTOR) expressions in the rat hippocampal CA1 region following chronic cerebral hypoperfusion (CCH) induced by permanent bilateral common carotid arteries occlusion (2VO). The mTOR immunoreactivity in the pyramidal neurons and mTOR protein level in the hippocampal CA1 region were markedly decreased at 21 and 28 days after 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…It has been well known that CCH can lead to cognitive impairment as well as neuropathological alterations in some brain regions including hippocampus and cerebral white matter ( Farkas et al ., 2004 , 2007 ; Yang et al ., 2014 ; Ueno et al ., 2015 ; Lee et al ., 2016a ). Especially, among some brain regions, the hippocampal CA1 region is thought to be one of the most vulnerable region following CCH ( Farkas et al ., 2004 ; Cechetti et al ., 2012 ; Lee et al ., 2016a ; Park and Lee, 2016 ). Some of underlying mechanisms, which related to the CCH-induced hippocampal neuronal damage, have been suggested to include oxidative stress and neuroinflammation ( Cechetti et al ., 2012 ; He et al ., 2012 ; Qu et al ., 2014 ; Lee et al ., 2016a ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been well known that CCH can lead to cognitive impairment as well as neuropathological alterations in some brain regions including hippocampus and cerebral white matter ( Farkas et al ., 2004 , 2007 ; Yang et al ., 2014 ; Ueno et al ., 2015 ; Lee et al ., 2016a ). Especially, among some brain regions, the hippocampal CA1 region is thought to be one of the most vulnerable region following CCH ( Farkas et al ., 2004 ; Cechetti et al ., 2012 ; Lee et al ., 2016a ; Park and Lee, 2016 ). Some of underlying mechanisms, which related to the CCH-induced hippocampal neuronal damage, have been suggested to include oxidative stress and neuroinflammation ( Cechetti et al ., 2012 ; He et al ., 2012 ; Qu et al ., 2014 ; Lee et al ., 2016a ).…”
Section: Introductionmentioning
confidence: 99%
“…Some of underlying mechanisms, which related to the CCH-induced hippocampal neuronal damage, have been suggested to include oxidative stress and neuroinflammation ( Cechetti et al ., 2012 ; He et al ., 2012 ; Qu et al ., 2014 ; Lee et al ., 2016a ). In addition, recent studies reported that a significant alterations of the mammalian target of rapamycin (mTOR) signaling pathway, such as decrease of phosphorylated mTOR (p-mTOR), occurred in the hippocampus following CCH ( Jia et al ., 2015 ; Park and Lee, 2016 ). However, the precise mechanisms about CCH-induced neuronal damage have not been fully elucidated yet.…”
Section: Introductionmentioning
confidence: 99%
“…mTOR can oversee multiple physiologic and disease processes such as cellular metabolism (69, 70), bone formation (71-73), diabetes (35, 43, 74-77), neurodegenerative disorders (37, 78-83), dementia (12, 84-86), and cancer (25, 27, 87-91). In addition, mTOR has a significant role in the modulation of autophagy induction (92).…”
Section: Circadian Rhythm Mtor and Sirt1mentioning
confidence: 99%
“…AD is not the result of a single etiology (42). Multiple mechanisms may lead to cognitive impairment and involve cellular injury from β-amyloid (Aβ), tau, excitotoxicity, mitochondrial damage, acetylcholine loss, astrocytic cell injury, oxidative stress, and cellular metabolic dysfunction with DM (14, 5157). Yet, there is a growing arsenal of novel therapeutic strategies directed against AD and other neurodegenerative disorders that include circadian rhythm clock genes (9), non-coding ribonucleic acids (RNAs), and the mammalian forkhead transcription factors of the O class (FoxOs) (56, 58, 59).…”
Section: Novel Nervous System Strategiesmentioning
confidence: 99%
“…mTOR also is known as the mammalian target of rapamycin and the FK506-binding protein 12-rapamycin complex-associated protein 1. mTOR controls multiple functions that determine the transcription of genes, proliferation and senescence of cells, protein formation, cellular metabolism, and cellular longevity (9, 57, 77, 129, 130). Melatonin, a pineal hormone that controls circadian rhythm, relies upon autophagy pathways and mTOR to control processes of aging and neurodegeneration (131).…”
Section: Circadian Clock Genesmentioning
confidence: 99%